Evolution of Fertilization-Related Genes Provides Insights Into Reproductive Health in Natural Ascrotal Mammals - Chai, Simin; Tian, Ran; Xu, Shixia; Ren, Wenhua; Yang, Guang (Frontiers in Ecology and Evolution, 2022)
Cryptorchidism is the failure of one or both testes to descend into the bottom of the scrotum. This common congenital malformation in humans and domestic animals is the best characterized risk factor for abnormal sperm functions and infertility. However, current treatment approaches for cryptorchidism do not ensure paternity in all cases. Some lineages of mammals (such as elephants and cetaceans) have natural ascrotal testes (i.e., undescended or incompletely descended testes) and normal sperm motility and fertility, providing an opportunity to understand the genetic basis of cryptorchidism. In this study, we showed that genes associated with sperm motility and competition/fertility in ascrotal mammals experienced frequent, strong selective pressure. The fixation of specific amino acids and positive selection in ascrotal mammals could affect the physicochemical properties and functions of fertilization-related proteins. In a comparison between mammals with undescended testes and incompletely descended testes, discrepancies in genes showing evidence for adaptive evolution and in functional enrichment suggested that multiple molecular mechanisms contribute to the maintenance of fertility in the challenging testicular environment. Our findings revealed substantial heterogeneity in the divergence of fertilization-related genes between natural scrotal and ascrotal mammals and provide insight into molecular mechanisms underlying normal sperm motility and competition in natural ascrotal mammals. We provide a detailed theoretical basis for understanding the pathology of cryptorchidism from a molecular evolutionary perspective. This study may contribute to the establishment of diagnostic and therapeutic targets for sperm motility and fertility disorders due to congenital cryptorchidism in humans and domestic animals.